Acute therapeutic effects and pathophysiology of eosinophilic granulomatosis with polyangiitis neuropathy - Fumitaka Shimizu; Mariko Oishi; Toshihiko Maeda; Yukio Takeshita; Hideaki Nishihara; Ryota Sato; Takashi Kanda; Masayuki Nakamori; Michiaki Koga; Miwako Fujisawa; Yuki Mizumoto; Nanami Yamanaka; et al. (BMJ Neurology Open)
Objective This study investigated the effects of early treatment and pathophysiology on eosinophilic granulomatosis with polyangiitis neuropathy (EGPA-N).Methods Twenty-six consecutive patients with EGPA-N were diagnosed and treated within a day of admission and underwent clinical analysis. Peripheral nerve recovery rates were evaluated after early treatment by identifying the damaged peripheral nerve through detailed neurological findings.Results The eosinophil count at onset was significantly correlated with the total number of damaged nerves. There was a strong correlation between the timing of treatment and the recovery rate in patients who started treatment within 50 days, as the recovery rate did not increase after 50 days of treatment. Antineutrophil cytoplasmic antibodies (ANCA)-negative cases showed significantly higher recovery rates than ANCA-positive cases. Vasculitis was detected in 67% of ANCA-positive and 29% of ANCA-negative patients in the sural nerve and skin biopsy specimen. In addition, infiltration of eosinophils into peripheral nerve tissues was observed in 40% of ANCA-negative patients, whereas it was absent in ANCA-positive patients. Intrafascicular oedema was found in 95% of all patients.Discussion Our results suggest three pathological pathways: (1) ischaemic peripheral nerve due to vasculitis mainly in ANCA-positive cases, (2) direct infiltration and degranulation of eosinophils in ANCA-negative cases and (3) progression of axonal ischaemia due to intrafascicular oedema in both cases. The study also found that ANCA-negative cases exhibited better responsiveness to acute-phase treatment than ANCA-positive cases. It is essential to treat patients with EGPA-N as early as possible because the patients could recover time-dependently within 50 days of the onset.